Open Ateliers 1998. - van Broeckhoven, Jan (Antwerpen : Personal Blue vzw, 1998)
Speybrouck, Raf ; Van Dyck, Anna Maria ; Tomballe, Gerard ; Bollansée, Marie Julia ; Levandesi, Bart ; De Croock, Peter ; Cruz Mena Pavaõ, José-Paul Da ; Moons, Kristin ; Schelkens, Dirk ; Verhoeven, Ingrid ; Van Daele, Lydia ; de Koninck, Peter ; Bausart, Lucie ; Stegmann, Inge ; Swerts, Ann ; Van Kerckhove, Lynda ; Perbal, Vincent ; Lotens, Gwenny ; De Vries, Mascha Marella ; Mattues, Walter ; Blockx, Linda ; Malfliet, Erwin ; Lancsweert, Bea ; Dankwa, Nana ; Marneffe, Chantal ; Siebeck, Oliver ; Klapchi ; Meeren, Jacky Van der ; Coen, Jean ; Van Camp, Ben ; Boogerman, Rudolf ; De Belder, Inge ; Hamzic, Azra ; Van Nunen, Rik ; Fontein, Cora ; Verheyen, Chris ; Hascic, Marcel ; Bosschaerts, Werner ; Lobel, Marc ; Shapir-Aran, Tsvia
adres, biog., tent. per kunstenaar + kleine tekst
Nederlands
Open Atelier 1998, Stad Antwerpen, 12, 13, 19 en 20 september 1998
boek
Keywords: Antwerpen